Hubungan Motivasi Belajar dengan Hasil Belajar Pendidikan Pancasila Peserta Didik Kelas V SDN 05 Batu Taba, Kabupaten Tanah Datar - Sari, Dina Puspita; Waldi, Atri (Lembaga Yasin AlSys, 2024)
This research was motivated by the low learning motivation of class V students at SDN 05 Batu Taba. This type of research is correlational research with a quantitative approach. The population in this study was all 20 class V students at SDN 05 Batu Taba. The sampling technique used is a saturated sampling technique, where all members of the population are sampled. Data collection techniques include questionnaires, tests, documentation. The results of the research show that there is no positive relationship between learning motivation and Pancasila education learning outcomes for class V students at SDN 05 Batu Taba, Tanah Datar Regency. This is proven by the calculated t value being smaller than the t table, namely 1.54 < 1.734 so that H0 is accepted and H1 is rejected.